Parental and Infant Gender Factors in Parent–Infant Interaction: State-Space Dynamic Analysis - Cerezo, M. Angeles; Sierra-García, Purificación; Pons-Salvador, Gemma; Trenado, Rosa M. (Frontiers in Psychology, 2017)
Abstract This study aimed to investigate the influence of parental gender on their interaction with their infants, considering, as well, the role of the infant’s gender. The State Space Grid (SSG) method, a graphical tool based on the non-linear dynamic system approach (NDS) was used to analyze the interaction, in Free-Play setting, of 52 infants, aged 6 to 10 months, divided into two groups: half of the infants interacted with their fathers and half with their mothers. There were 50% boys in each group. MANOVA results showed no differential parenting of boys and girls. Additionally, mothers and fathers showed no differences in the Diversity of behavioral dyadic states nor in Predictability. However, differences associated with parent’s gender were found in that the paternal dyads were more "active" than the maternal dyads: they were faster in the rates per second of behavioral events and transitions or change of state. In contrast, maternal dyads were more repetitive because, once they visited a certain dyadic state, they tend to be involved in more events. Results showed a significant discriminant function on the parental groups, fathers and mothers. Specifically, the content analyses carried out for the three NDS variables, that previously showed differences between groups, showed particular dyadic behavioral states associated with the rate of Transitions and the Events per Visit ratio. Thus, the transitions involving ‘in-out’ of ‘Child Social Approach neutral - Sensitive Approach neutral’ state and the repetitions of events in the dyadic state ‘Child Play-Sensitive Approach neutral’ distinguished fathers from mothers. The classification of dyads (with fathers and mothers) based on this discriminant function identified 73.10% (19/26) of the father-infant dyads and 88.5% (23/26) of the mother-infant dyads. The study of father-infant interaction using the SSG approach offers interesting possibilities because it characterizes and quantifies the actual moment-to-moment flow of parent-infant interactive dynamics. Our findings showed how observational methods applied to natural contexts offer new facets in father versus mother interactive behavior with their infants that can inform further developments in this field.